Description of Dental and Oral Health Maintenance Behavior of Elementary School Students - Katili, Laurencia; Anindita, Pritartha S.; Juliatri, Juliatri (e-GiGi, 2022)
Abstract: The 2018 Basic Health Research (Riskesdas) stated that the prevalence of students with dental and oral problems in North Sulawesi showed a fairly high number, which was 66.5%. In children, behavioral factors that ignore dental and oral hygiene could affect the development of dental and oral health. Behavior can be measured byÂ  using three domains, namely knowledge, attitudes, and actions. This study aimed to obtain the description of dental and oral health maintenance behavior of elementary school students. This was a descriptive study with a cross sectional design. Population of this study were students at the elementary school SDN 1 Bulawan East Bolaang Mongondow, North Sulawesi, Indonesia. Meanwhile, samples were students of grades 5-6 totaling 44 children obtained by using total sampling method. Data were collected by using an online oral health maintenance behavior questionnaire via googleform. The results showed that the measurement scores were as follows: category of knowledge was 405; category of attitude was 394, category of action was 396, with a total score of 1195. In conclusion, the behavior of dental and oral health maintenance of students at SDN 1 Bulawan is classified as good.Keywords: behavior; dental and oral health maintenanceÂ Abstrak: Riset Kesehatan Dasar (Riskesdas) 2018 menyebutkan bahwa prevalensi siswa yang bermasalah gigi dan mulut di Sulawesi Utara menunjukkan angka yang cukup tinggi yaitu sebesar 66,5%. Pada anak faktor perilaku mengabaikan kebersihan gigi dan mulut berpengaruh terhadap perkembangan kesehatan gigi dan mulut. Perilaku dapat diukur dengan tiga domain yaitu pengetahuan, sikap, dan tindakan. Penelitian ini bertujuan untuk mendapatkan gambaran perilaku pemeliharaan kesehatan gigi dan mulut siswa sekolah dasar. Jenis penelitian ialah deskriptif dengan desain potong lintang. Populasi penelitian ini yaitu siswa di SDN 1 Bulawan, Bolaang Mongondow Timur, Sulawesi Utara. Sampel penelitian yaitu anak SDN kelas 5-6 berjumlah 44 orang. Teknik pengambilan sampel yang digunakan metode total sampling. Pengumpulan data menggunakan kuesioner perilaku pemeliharaan kesehatan gigi dan mulut secara online melalui googleform. Hasil penelitian mendapatkan bahwa skor hasil pengukuran kategori pengetahuan sebesar 405, kategori sikap 394, kategori tindakan 396, dengan skor total 1195. Simpulan penelitian ini ialah gambaran perilaku pemeliharaan kesehatan gigi dan mulut siswa SDN 1 Bulawan tergolong baik.Kata kunci: perilaku; pemeliharaan kesehatan gigi dan mulut